An Introduction to Riemannian Geometry: Una Introducción a la Geometría Riemanniana - Sánchez M, José M. (2020)
The main purpose of this article is to make a historical introduction to Riemannian Geometry, highlighting the renewed validity of this mathematical area of research. It is a branch full of interesting examples of application in the reality that surrounds us, which can range from the use of spherical geometry in the geolocation of our GPS, to the application of the theory of general relativity and the interpretation of how our universe expands.